Automation of Train Cab Front Cleaning with a Robot Manipulator - Moura, João; McColl, Willam; Taykaldiranian, Gerard; Tomiyama, Tetsuo; Suphi Erden, Mustafa (Cranfield University, 2018)
This files gives a short description of the data used to produce the plots of the paper submitted to review.Besides the data files, we are only submitting the pdf file (CASE2018.pdf) and the accompanying video (CASE2018.mp4).NB. CASE2018.pdf cannot currently be uploaded here but see related article at https://doi.org/10.1109/LRA.2018.2849591 and conference site at http://case2018.org/.The data files can be found in the data_plots folder.The files have the extension *.dat, and the data is separated by a space.Each column of the files correspond to a different measured variable and the rows correspond to the measurements over time.The files are the following:baxter_raster_large.datbaxter_raster_small.datbaxter_spiral.dattrain_raster_large.dattrain_raster_small.datWhere train refers to the experiments done with the functional prototype on the scaled front train.Baxter refers to the experiments done with the Baxter in the curved surface.Raster and spiral refer to the pattern of motion used, and large and small refer to the radius of the raster scan - distance between the parallel lines.The first line of each files indicates the measurement quantities for each column, where:The forces (fx,fy,fz) are measured in Newton.The torques (mx,my,mz) are measured in Newton meter.The positions (x,y,z) are measured in meters.The reference positions (xref,yref,zref) are measured in meters.The time is measured in seconds.
Keywords: 'Kinematics'; 'industrial robots'; 'motion control'; 'force control'; 'Control Systems; Robotics and Automation'